Promises of Democratic Consent and Practices of Citizenship - Mattia Arioli (JAm It!, 2022)
On June 26, 2017, the U.S. Supreme Court upheld Proclamation 9645, also known as the “Travel Ban” or “Muslim Ban.” This resolution suspended the insurance of immigrant and non-immigrant visas to applicants from Libya, Iran, Somalia, Syria, and Yemen (which are Muslim-majority countries), plus North Korea and Venezuela. Because of Donald Trump’s decision, many American had their rights diminished: spouses were separated; children could not reunite with their parents; students felt hopeless about getting a job in the U.S.; and many felt trapped, unable to leave America for fear of not being able to reenter the country despite their legal status. The Supreme Court validated the executive branch’s ability to limit people’s freedom and many of their (internationally recognized) rights in the name of national security. People from the ‘banned’ countries were blocked from seeking asylum independently from their living conditions (Gladstone & Sugiyama, 2018: web). This event had the involuntary effect of revitalizing the memory of an old court case, the well-known Korematsu v. United States, and the haunting ghost of the Japanese internment camps. In both cases (Trump’s Proclamation 9645 and Franklin Delano Roosevelt’s Executive Order 9066), claims to national security were used to justify and mask ethnic, racial (and religious) animus. The lack of respect for individuals’ access to justice, in spite of their citizenship, the racist undertones present in both misinformed propaganda rhetorics, and the malicious detention of individuals are clear parallelisms connecting these two events (Wietelman, 2019). These correspondences were also (shamelessly) noticed by a pro-Trump Great American PAC spokesperson, who cited Japanese internment camps as ‘precedents’ for Muslim registry (Hartman, 2016: web). Likewise, the opposition often cited Korematsu as a notably bad decision and antecedent. For example, Justice Sotomayor manifested his dissent by comparing the ‘Travel Ban’ decision to Korematsu v. United States. Indeed, in both cases, one might question the constitutionality of means to separate neatly the “bad actors” from the larger group. In the Executive Order 9066, all persons of Japanese ancestry living in the western United States were part of the larger group, whereas the “bad actors” were citizens deemed to be disloyal. In Trump’s Proclamation 9645, the citizens of only eight countries composed the larger group, and the “bad actors” were those considered potential terrorists within that population. In both situations, the Court “abandoned judicial review over alleged infringement of constitutional rights asserted by American citizens arising from screening procedures” (Dean, 2018:176). This led many American to infer that Trump v. Hawaii was a reiteration of the Korematsu case. Given this context, it no surprise to see the reenactment of Japanese internment camps in contemporary graphic novel. Thus, these works can be seen as “memory projects” (Leavy, 2007) as they activate particular repositories of collective memory in order to bring certain aspects of the recent past into the public eye. These projects might be seen as attempts to resist dominant records of the event, allowing individual voices and (hi)stories to arise, as well as a means to disseminate new ideas about activism and citizenship. The choice of the medium is not neutral as it might be seen as an homage to one of the earliest vivid testimony of the Japanese incarceration, Miné Okubo’s (1946) Citizen 13660. Yet, it is important to remark that in the 1940s the medium comics was also involved in the dissemination of anti-Japanese and Anti-Asian sentiments. Finally, whereas previous revocations of the event in comic form aimed to make the public aware of present injustices (Okubo, 1946), denounce America’s long history of Asians’ exclusion policy (Yang et al. 2009) and counter the invisibility of Asians’ sufferings (Toyoshima, 2003), the more recent comics do not just aim to address these old questions, but to bring these debates within a “global civil sphere” (Alexander, 2012).